Comparative Analysis of Innovative Activity Determinants in Companies of Small and Medium Enterprises Sector in Brazil and Poland. Results of empirical researches - Tomasz Norek; Daniel Luis Arenhardt (Institute of Economic Research (IER), 2014)
The basic goal of this article is an attempt to conduct comparative analysis of innovation determinants in companies of small and medium enterprises sector in Brazil and Poland. The comparison shall enable evaluation which determinants stimulate and which are barriers to innovativeness development in the SME sector in the researched countries. Additionally, such comparison shall indicate if and in what way the economical potentials, cultural differences and different historical conditions of the economic development of the researched countries influence the determinants of the innovative activity of the SME sector. The Authors put forward the following research hypothesis: H1: The determinants forming the innovative potential are similar for Brazilian and Polish companies of SME sector. In order to examine the hypothesis, the Authors have browsed the world literature on the subject of innovative actions determinants in companies with a special consideration of SME sector companies, they have presented the present condition of innovativeness in SME sector companies in Brazil and Poland (an Internet questionnaire has been used in the research) and they have conducted own empirical researches on the determinants influencing the innovativeness level. The received results have been subject to basic statistical comparative analysis and on this basis with the logical induction the Authors have made conclusions on the determinants of innovative activity in researched companies. The article includes the results of all the empirical researches conducted by the Authors in the years 2009-2013 and generally available data considering the innovativeness level in the researched countries.
Keywords: O10; O30; O50; O57; 330; innovative SMEs; determinants of innovation activity; SMEs in Brazil and Poland